Wokół problemu wznowienia obrad IV Forum polsko-niemieckiego w listopadzie 1985 roku = Around the problem of resuming the meetings of the IVth Polish-German Forum in november 1985 - Świder, Małgorzata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The Polish-German Forum, which was instituted in 1976, became a platform of talks and bilateral consultations. Following the imposition of the Martial Law in Poland, its activity was suspended. Due to the significance of the Forum, a series of actions were undertaken both in the Polish People`s Republic and the Federal Republic of Germany, with the aim to eliminate unfavorable opinions which were detrimental to resuming its works. That concerned especially Christian Democratic politicians` public utterances relating the issue of the Polish-German border and the German minority in Poland, or the lack of agreement for representatives of licensed Polish trade unions to participate in the Forum.
Keywords: stosunki polsko-niemieckie; polityka międzynarodowa; po 1944 r.; stan wojenny w Polsce (1981-1983); polish-german relationships; international politics; the martial law in Poland